Association between trauma patients' severity and critical care nursing workload in China. (30th March 2014) - Peng, Lingli; Mayner, Lidia; Wang, Honghong
Abstract The correlation between patients' severity and nursing workload for multiple trauma patients within the first 24 h of admission was explored in this study. Multiple trauma adult patients (n = 229) admitted in the emergency rescue room of a public hospital in China over a 1 year period were enrolled in this study. The worst values of the Acute Physiology and Chronic Health Evaluation‐II scores and the Nursing Activity Score were collected during the first 24 h after admission. The predicted number of registered nurses was calculated for the corresponding severity groups. In the results, one‐way ANOVA revealed that the Nursing Activity Score in the seven severity groups differed significantly. The total Acute Physiology and Chronic Health Evaluation‐II score had a positive correlation with the Nursing Activity Score. The predicted number of registered nurses required was 0.6 for the low group, 0.7 for the moderate group, 1.0 for the severe group, and 1.1 for the extremely severe group. Patients' illness severity is an important indicator of nursing workload, especially in nurse staff allocation within the emergency department.